Kearifan Ekonomi: Refleksi Pemikiran Ekonomi Kerajaan Islam di Indonesia (Sumatera dan Kalimantan) - Pamungkas, Danu; Hidayati, Tri (Yayasan Rahmat Islamiyah, 2025)
This article analyzes the economic wisdom embedded in islamic thought of the kingdoms of sumatera and kalimantan. By employing a library research approach with a socio-political historical perspective, it examines how islamic teachings shaped the economic practices, social values and governance in these regions. The discussions reveal that the integration of islamic principles with local customs fostered the developement of a fair and sustainable aconomic system. This artcle highlights the lasting influence of islamic economic practices and wealth redtribution within these histrocal islamic kongdomns.